(untitled) (Fiep Bulletin - online, 2014)
The effect of the ingestion of a balanced feeding, associated to practical the regular one of exercise are vital to the physiological balance and consequently it reflects in the health of the individual. The objective of this study was to verify the profile of the level of physical activity and composition of the diet in practicing adult individuals of the masculine sex of swimming. Ratio of macronutrients of the diet (VASCONCELLOS, 1993) and the energy demand (BOUCHARD et al, 1983) in 11 practitioners of swimming was verified it (21,23 ± 4,26 years). Of general form the swimmers had moderately presented to be active. The protein ingestion was 7.27% above of the consumption standards, had demonstrated to consume a lesser ratio of carbohydrates (53.81%) in the diet and amounts recommended for the health of lipids (27.79%). The sample demonstrated a negative energetic equilibrium, where it caloric arrives in port does not correspond of ideal form to the objectives of the swimmers.